Why Go NANO on COVID-19 Pandemic? (2020)
Although treating COVID-19 is shown to be challenging, NANOtechnology is around the corner to overcome potential drawbacks. The use of NANOtechnologies will definitely shape the worldwide approaches and tools to treat COVID-19. Here we highlight the importance of going NANO on the COVID-19 pandemic.